Fabrication and evaluation of nanomaterial based electrochemical sensor for robust detection of lithium - Lamba, Ravinder; Bhanjana, Gaurav; Dilbaghi, Neeraj; Gupta, Vivek; Kumar, Sandeep (Frontiers in Nanotechnology, 2025)
Introduction: Lithium plays an important role in the modern technology-driven world, as it is an essential component of numerous renewable energy devices such as solar panels, wind turbines, and electric vehicles. The usage of lithium has increased in portable electronics, as a catalyst in the medical field, and various other applications that have increased its demand gradually in recent years. The harmful effects of the extraction and disposal of lithium need to be considered simultaneously along with exploring its applications in numerous frontier areas. The methods employed for lithium extraction can lead to air and water pollution, land degradation, and pose a risk of groundwater contamination. Therefore, the quantification of lithium ions through easy, quick, reliable, and affordable methods is highly desired.Methods: Herein, a reliable and fast response electrochemical sensing strategy has been employed using Ag-doped Co3O4 nanochips (Ag@CNCs) for lithium detection in field samples. Hexahydrate cobalt nitrate [Co(NO3)2·6H2O] has been used as a precursor for the synthesis of Ag@CNCs through the co-precipitation method followed by calcination.Results and discussion: The synthesised Ag@CNCs have a face-centred cubic structure, with an average crystallite size of 14.7 nm as evidenced through x-ray diffraction analysis. Further, Ag@CNCs exhibit two distinct band gap energies (Eg) of 1.55 eV and 2.08 eV corresponding to two absorption peaks in the UV-visible spectrum. The developed electrochemical sensor by utilising Ag@CNCs exhibited remarkable electrocatalytic performance for lithium detection, attaining a high sensitivity of 78.66 μAmM−1cm−2 and a notable limit of detection of 5 μM, enabling direct quantification without requiring pretreatment.